Capturing conflicting accounts of domestic labour: The household portrait as a methodology - Christopher, Emily (Sociological Research Online, 2020)
Drawing on data from a UK study conducted in 2014/2015, based on qualitative interviews with 25 working parent, heterosexual couples on their domestic division of labour, I argue that the interactive methodology of the ‘Household Portrait’ not only provides data on the distribution of household labour but also reveals gender differences in how domestic labour is conceptualised and measured. Disagreements and inconsistencies between couples over who ‘mostly’ does various tasks embody gendered perceptions of the meaning of doing domestic tasks and the appropriate temporal frame for evaluating individual contributions. Partners’ joking competition over their respective contributions highlight not just the normative expectations guiding what women and men feel they should do but also the criteria that they think should be used to measure their contributions. © The Author(s) 2020.
Keywords: approches et analyses; charge mentale; couple hétérosexuel; discipline; europe; famille; projet charge mentale; royaume-uni; régions géographiques; répartition des tâches domestiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique